The Effect of Consumer Intention on the Growth of the Use of E-Wallet as a Cash Substitute in Indonesia - Soewandi, Ayu Meity Siswanti; Gosal, Gandi Krisyan; Sitompul, Indana Ulfah; Damayanti, Nur (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The growth in the use of electronic money in Indonesia has been very rapid since it was first released in 2009. In 2021, the number of electronic money transactions in Indonesia Rp. 305.4 trillion. This figure is likely to continue increase every year. The influence of consumer intentions is believed to have a large impact on the growth in the use of electronic money. This study aims to analyse the effect of perceive usefulness, perceived ease of use and perceived of risk covid-19, attitude towards using on intention to use. The total number of respondents used in this study was 417 respondents. This study also uses the purposive sampling method by determining the sample based on the use of e-wallet starting from gender, age, marital status, education, monthly income and how often the e-wallet is used. Based on the results and testing of the data in this study, we found that the data had validity and reliability that met the requirements. Based on the results of the R Square test and hypothesis testing, we found that each variable that must be studied has a positive and significant relationship. It is shown that the perceive usefulness, perceive ease of use, perceive risk of covid-19 and attitudes towards the use of e-wallet have a big influence on intention to use. This research is only limited to users of the e-wallet transaction tool and the results of the study cannot be generalized to other fintech applications, because the name of the company that makes the fintech product can also affect the respondents' answers. Further research, researcher suggest adding other variables that have not been used in this study, such as perceived security and innovative users.